O ENSINO DE CANCEROLOGIA NAS FACULDADES DE ODONTOLOGIA DO BRASIL - Garrafa, V.; De Castro, A. L.; Garrafa, I. R.U. (My University, 1973)
A total of 512 questionnaires, each one including 23 questions, was used. They were answered by advanced students from 18 dentistry schools. The questions dealt with the basic principles of teaching oral cancerology. After analyzing the answers, several hypotheses about the framing of an odontologic curriculum are discussed. The teaching methods related to oral cancer were also considered. Based on the methods employed and on the results obtained, it is concluded that: the new dentists are not being properly prepared in the cancerology field and because of the high incidence of oral cancer in Brazil, special attention must be given by the responsible persons for the teaching of this subject.
The cancerology teaching in Brazilian schools of dentistry